Komunitas Sebagai Agen Perdamaian: Pengukuran Batas Etnik sebagai Variabel Kajian Relasi Etnik di Alor Star, Malaysia dan Padang, Indonesia - Khaidir , SH., M.Hum, MAPA, Ph.D, Afriva (TINGKAP, 2010)
ABSTRACT Social structure of society in Malaysia and Indonesia is a product of politic and colonial policy in the past. By relation among limited ethnic based on the form of plural society, both of these countries grow into new countries and the problems of ethnic become an important agenda in the process of countries development. As an indegene ethnic who has put on the edge, Malay race live side by side with some other ethnics like Chinese. Relationship among ethnics will develop easily become potential conflict without public administration in good government level.Using mixing methods among the surveys, focus group discussion, deep interview and ethnography observation in Alor Setar and Padang, this research is focused on searching the pattern on Neighborhood Association which is active and non active. It is also categorized based on the evaluation of government instance who has guided Neighborhood Association. Generally, the findings theory show that Neighborhood Association who is actively giving chances and choices to the citizen among ethnics and work out intensively. Minority of Chinese ethnic shows the level of good involvement, as Malay ethnic. They feel secure in their daily activities. Daily relationship and the institutions give the closeness among the citizen by doing some programs. Neighborhood Association do not emphasize the safety need and government agency in administrative sector just like in the beginning of its forming. It has reinforced the community although less economic efforts have done. Citizens’ understanding about organization development in the future do not found yet Kata Kunci: Neighborhood associations, community, social structure, ethnic relations, peace studies